Metal recovery from jarosite waste – A resin screening study - Riley, Alex L.; Pepper, Sarah E.; Canner, Adam J.; Brown, Solomon F.; Ogden, Mark D. (Separation Science and Technology (Philadelphia), 2018)
Work has been carried out screening hydrometallurgical resins for application in the valorization of industrially produced jarosite. Of the seven resins tested, anion exchange resins performed poorly for valuable metal recovery. Purolite S950+ and S957, along with a strong acid resin, show good extraction properties, but are selective for Fe over the other (divalent) metals. Purolite S930+ (iminodiacetic acid-functionalized resin) demonstrates selectivity for Cu over Fe , but poor selectivity for Ni , Zn , and Co . Dowex M4195 (bispicolylamine-functionalized resin) demonstrates promise for extracting metals of value away from a mixed metal pregnant liquor solution (PLS). A three-stage column-based recovery process is proposed for jarosite leachate treatment. 3+ 2+ 3+ 2+ 2+ 2+
Keywords: Ion exchange; Resource recovery; Extraction; Transition metals; Acid mine drainage